Meningkatkan Pemahaman Ayat-Ayat Hukum Waris Dan Mu’amalah Pada Santri Di Pondok Pesantren Qur-any Jombang - Moch. Sya'roni Hasan; Qurrotul Ainiyah; Muhammad Anas Ma’arif (An Naf'ah: Jurnal Pengabdian Masyarakat, 2023)
The purpose of this service is to describe the training and assistance of students in understanding the verses of inheritance law and mu'amalah at the Qur-any Jombang Islamic boarding school. The method of implementation is that prior to the implementation of training and mentoring, a literature study is first carried out on various ways of organizing the funeral, preparation of tools and materials for the practice of organizing the funeral, determines the time of implementation and the duration of the community service activities together with the implementation team, determines and prepares material to be delivered in community service activities. The result of this service is that the students can read, interpret, analyze, know the law and practice the verses of the Qur'an regarding the Law of Inheritance and Mu'amalah properly and correctly. The students' knowledge and understanding of the verses of the Qur'an concerning the law of inheritance and mu'amalah increased the activities, so that the activities took place smoothly and effectively. The inhibiting factor is the limited training time.